Utilizing Google trends to monitor coronavirus vaccine interest and hesitancies. Issue 30 (26th June 2022) - Merrick, Emily; Weissman, Joshua P.; Patel, Sameer J.
Highlights: Google Trends was utilized to analyze search interest for terms related to COVID-19 misinformation, general misinformation, and access throughout the pandemic. Search interest in these categories shifted in relation to events taking place throughout the pandemic. The most commonly searched terms in each subgroup were: "Covid vaccine infertility", "Covid vaccine side effects", and "Covid vaccine appointment". Google trends can be used to monitor trends in public attitudes and misinformation regarding COVID-19 vaccines and target education. Abstract: Introduction: Vaccine hesitancy remains a serious challenge for ending the coronavirus disease 2019 (COVID-19) pandemic. Digital media has played an immense role in the spread of information during the pandemic. One method to gauge public interest in COVID-19 related information is to examine patterns of online search queries. Methods: Google Trends (GT) was used to analyze results for search terms relating to COVID-19 vaccine misinformation, information, and accessibility from October 1st, 2020 to May 27th, 2021. GT allows you to compare multiple queries at one time. The resultant relative search volumes (RSVs) range from 0 to 100. The search term and point in time on the graph that has the greatest search volume is given a score of 100 and all other terms and times are given values relative to that maximum. Search interest peaks were analyzed by subgroups (misinformation, information seeking, and access seeking) and across key time points throughout the pandemic. Results: GT analysis revealed that search interest related to vaccine misinformation, general information, and access seeking changed in relation to events taking place throughout the pandemic. The most commonly searched terms in each subgroup were: "Covid vaccine infertility", "Covid vaccine side effects", and "Covid vaccine appointment". Searches related to misinformation peaked in December 2020. Search terms in the general information category peaked in April 2021. RSVs for access seeking terms peaked in March 2021 and have decreased since April 2021. Conclusion: Misinformation RSVs were highest after FDA authorization and have multiple repeated spikes after subsequent vaccine announcements. General information seeking terms peaked concurrently with increased vaccination uptake in the United States. Search interest has decreased with wider vaccine availability, despite many individuals in the United States remaining unvaccinated. GT can be used to monitor trends in public attitudes and misinformation regarding COVID-19 vaccines and further target education.